Rozw2rownanie:
3 - x = 2x + 1
5x - 5 = 16 - 2x
5(x-7) + 2 = -28
2(x - 1) + 3(x + 1) = 26
4x - 3(3x - 5) = 6x + 4
8-(4x - 12) = 8x -(3x - 2)
-(x+1)+ 8x = 5x - 9


Odpowiedź :

Odpowiedź:

3 - x = 2x + 1

-x +2x = 1-3

x= -2

5x - 5 = 16 - 2x

5x +2x = 16 +5

7x= 21/:7

x=3

5(x-7) + 2 = -28

5x -35 +2 = -28

5x = -28 + 35 - 2

5x = 5/:5

x=1

2(x - 1) + 3(x + 1) = 26

2x-2+3x+3=26

5x=26+2-3

5x=25/:5

x=5

4x - 3(3x - 5) = 6x + 4

4x-9x+15=6x+4

4x-9x-6x=-15+4

-11x= -11/: (-11)

x = 1

8-(4x - 12) = 8x -(3x - 2)

8 -4x+12= 8x-3x+2

-4x-8x+3x= -8-12+2

-9x= -18/: (-9)

x = 2

-(x+1)+ 8x = 5x - 9

-x-1+8x =5x-9

7x-5x=-9+1

2x=-8/:2

x = -4